Form factors of consumer crediting - cash or a credit card? - D. V. Agrba (Путеводитель предпринимателя)
In the conditions of unstable economic situation raises the question of choice of financial products that will be relevant and useful in these circumstances. Lending is one of the core activities of commercial banks, however, the choice of type of lending, composition of the loan portfolio and the method of its management in rapidly changing market conditions require that banks are highly professional and error-free approach of choice, «to bet».